Musicians and researchers: two creative professions striving to improve heart health through music - Pozzati, Andrea; Weiskirchen, Ralf (Frontiers in Cardiovascular Medicine, 2025)
Musicians and researchers are creative professions that share many similarities. They both aim to bring joy and progress to humanity. In recent decades, it has been shown that music has the ability to alleviate pain, improve heart function, reduce anxiety, and stimulate the release of endogenous opioids in the brain. This has led to the emergence of music therapy as a popular therapeutic option for supporting and regulating cardiovascular health, emotional, cognitive functions, and mental wellbeing. Similarly, translational researchers and clinicians strive to generate new medical knowledge and effective treatments for various diseases. In their daily work, both musicians and scientists engage in the development of new ideas, concepts, and visions. They explore and experiment to find the best way to create something novel. Furthermore, driven by discovery, curiosity, and a deep longing, they strive to make a significant impact on heart health. In today's world, artificial intelligence technology plays an increasingly important role in achieving these goals in both fields. Success is measured by publications in esteemed journals or achieving high rankings on music charts. This review explores the similarities between researchers and musicians and how music therapy can aid in the treatment of specific symptoms related to heart function.